2022
DOI: 10.1038/s41572-022-00342-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive eye disease

Abstract: Hypertensive eye disease includes a spectrum of pathological changes, the most wellknown being hypertensive retinopathy. Other commonly involved parts of the eye in hypertension include the choroid and optic nerve, sometimes referred to as hypertensive choroidopathy and hypertensive optic neuropathy. Together, hypertensive eye disease develops in response to acute and/or chronic elevation of blood pressure. Major advances in research over the past three decades have greatly enhanced our understanding of the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 284 publications
0
29
0
Order By: Relevance
“…Recent studies have found that optic nerve damage from hypertension is prevalent in the general adult population. 19 The availability of noninvasive OCT allows the examination of these alterations and their value in hypertension management and dementia risk stratification. This study analyzed the effects of BP and arterial stiffness on RNFLT and GCIPLT, including macular and optic disc area parameters, in two large cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that optic nerve damage from hypertension is prevalent in the general adult population. 19 The availability of noninvasive OCT allows the examination of these alterations and their value in hypertension management and dementia risk stratification. This study analyzed the effects of BP and arterial stiffness on RNFLT and GCIPLT, including macular and optic disc area parameters, in two large cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Signs of hypertensive retinopathy, such as focal arteriolar narrowing, arteriovenous nicking, haemorrhages, microaneurysms and exudates, are well known to be related to CVD [16 ▪ ]; however, there are no existing deep learning models to detect hypertensive retinopathy signs from retinal photographs automatically.…”
Section: Applications Of Artificial Intelligence In Retinal Photograp...mentioning
confidence: 99%
“…Studies demonstrated parallel pathological changes morphologically between the retinal vasculature and the coronary and cerebral vasculatures [8 ▪ ,13–15]. Traditionally, retinal vascular changes were assessed via qualitative and quantitative parameters from ophthalmic examination and retinal photographs with semi-automated software [16 ▪ ]. Qualitative measurements include focal arteriolar narrowing, arteriovenous nicking, and retinopathy signs such as microaneurysms, haemorrhage and exudates, while quantitative measurements include retinal vessel calibre, tortuosity, bifurcation angle, tortuosity and fractal dimension [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertensive patients experience continuous contraction and tension of systemic arterioles. Long-term hypertension can cause arterial lumen stenosis, subsequently leading to hypertensive arteriosclerosis, resulting in retinal vascular stenosis thinning [18,19]. In the early stages, the fundus of patients with hypertension may not show any pathological changes.…”
Section: Application Of Ai Image Analysis In Hypertensivementioning
confidence: 99%